2012
DOI: 10.1055/s-0032-1327651
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Cholesterol Subfractions and Lecithin: Cholesterol Acyltransferase Activity in Collegiate Soccer Players

Abstract: Many of the published data on the lipid profile of athletes is based on studies of endurance athletes. The data on soccer players are rare. The purpose of this study was to examine serum high-density lipoprotein cholesterol subfractions and lecithin:cholesterol acyltransferase activity in collegiate soccer players. 31 well-trained male collegiate soccer players were divided into 2 groups: 16 defenders and 15 offenders. They were compared with 16 sedentary controls. Dietary information was obtained with a food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In their guidelines for daily CHO intake for soccer players, Burke and coworkers differentiate between “mobile” and “less mobile” players based on the nutritional demands associated with their playing position [34]. However, there is little information available about the food and nutrient intake of soccer players relative to their field position (Table 4) [43,101,102,103]. Moreover, some of these articles do not provide information for the entire team, and thus are not included in Table 1.…”
Section: Correlates Of the Eating Practice And Nutritional Intake mentioning
confidence: 99%
“…In their guidelines for daily CHO intake for soccer players, Burke and coworkers differentiate between “mobile” and “less mobile” players based on the nutritional demands associated with their playing position [34]. However, there is little information available about the food and nutrient intake of soccer players relative to their field position (Table 4) [43,101,102,103]. Moreover, some of these articles do not provide information for the entire team, and thus are not included in Table 1.…”
Section: Correlates Of the Eating Practice And Nutritional Intake mentioning
confidence: 99%
“…The beneficial effects are related to the prevention and or amelioration of cardiovascular risk factors such as dyslipidemia, hypertension, diabetes mellitus, and endothelial dysfunction ( Ficker et al, 2010 ; Cornelissen and Smart, 2013 ; Umpierre et al, 2013 ; Guizoni et al, 2016 ). Exercise reduces plasma triglycerides (TG), small dense low-density lipoprotein (LDL), increases high-density lipoprotein cholesterol (HDLc), and apolipoprotein A-I ( Halverstadt et al, 2007 ; Imamura et al, 2013 ; Sondegaard et al, 2014 ). In addition, it improves reverse cholesterol transport (RCT), a system that prevents atherogenesis by clearing the excess cholesterol from the arterial wall allowing its secretion into bile and feces excretion ( Nijstad et al, 2011 ; Rocco et al, 2011 ; Pinto et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both low and high intensity running and cycling exercises have been shown to produce beneficial adjustments to lipid profiles [10][11][12]. Furthermore, team sport training also presented improvements in concentration of TC, TAG, LDL-c, and HDL-c [13][14][15]. Some studies have already observed that soccer players under regular training present higher levels of HDL-c [4,16], and lower levels of LDL-c and TC [17] than match-related sedentary subjects.…”
Section: Introductionmentioning
confidence: 99%